2010
DOI: 10.3109/17453674.2010.548028
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of circulating HLA DR+CD8+T-cells and correlation with chromium and cobalt concentrations 6 years after metal-on-metal hip arthroplasty

Abstract: Background and purpose Following metal-on-metal hip arthroplasty (THA), immunological reactions including changes in lymphocyte populations, aseptic loosening, and lymphocytic pseudotumors occur. We hypothesized that changes in lymphocyte subpopulations would be associated with elevated metal ion concentrations.Methods A randomized trial involving 85 patients matched for age and sex and randomized to receiving metal-on-metal (n = 41) or metal-on-polyethylene total hip arthroplasty (n = 44) was conducted. 36 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…RCTs were generally small and included between 13 and 117 patients. Two RCTs examined MoM vs. ceramic-polyethylene (CoP) [32], [33], five studies MoM vs. metal-polyethylene (MoP) [34], [35], [36], [37], [38], [39], two studies examined MoM vs. ceramic-ceramic (CoC) [26], [40], [41], and two MoM vs. hip resurfacing arthroplasty (HRA) [42], [43], [44]. LH-THA was investigated in one US-American study [35].…”
Section: Resultsmentioning
confidence: 99%
“…RCTs were generally small and included between 13 and 117 patients. Two RCTs examined MoM vs. ceramic-polyethylene (CoP) [32], [33], five studies MoM vs. metal-polyethylene (MoP) [34], [35], [36], [37], [38], [39], two studies examined MoM vs. ceramic-ceramic (CoC) [26], [40], [41], and two MoM vs. hip resurfacing arthroplasty (HRA) [42], [43], [44]. LH-THA was investigated in one US-American study [35].…”
Section: Resultsmentioning
confidence: 99%
“…Cytotoxic T cells are frequently CD4+, although CD8+ T cells also participate in the pathology, and there is evidence of skewing of Vb T cell subsets in metal hypersensitivity [73]. Metal ions can act directly on immune cells and mediate toxic or stimulatory effects [3] including an increase in T cell costimulatory molecules [13] and elevated expression of the activated (CD3/CD69) T cell phenotype [28] and increased circulating HLA DR+ CD8+ T-cells [32]. The relationship between metal hypersensitivity and implant failure remains uncertain, because the immune response could contribute to the pathology or arise as a result of elevated ion exposure from wear particles generated as a metal component fails.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…Depending on the chemical properties of the biomaterial, there may be breakdown and corrosion products released, which may have both local and systemic effects [13,32,40]. The articulation of a joint prosthesis complicates this condition enormously, because the generation of wear is an inevitable consequence of movement at the bearing surface.…”
Section: Introductionmentioning
confidence: 99%
“…Participation of the adaptive immune system in host response to prosthetic wear debris is still a subject of controversy despite the fact that several reports have described lymphocytes in periprosthetic tissues, retrieved from patients with aseptically failed metal-on-metal (MoM) or non-MoM implants (Fujishiro et al 2011;Ng et al 2011). One recent study revealed increased serum concentration of cobalt and chromium in patients with MoM THA which positively correlated with increased proportion of HLA DR+ CD8+ T-cells in these patients (Hailer et al 2011). In the same study, it was proposed that macrophages around THA could create haptenic metal ions in the context of self peptides (metal ion-altered self) as antigens in combination with MHC class II molecules, leading to T-cell priming.…”
Section: Hierarchy Of Immune Reactions To Prosthetic Wear Particles (mentioning
confidence: 99%